Rekonstruksi Hubungan Nasab dan Hak Keperdataan Anak Luar Nikah dalam Hukum Keluarga Islam Indonesia: Perspektif Maqāṣid al-Syarī‘ah - Endah Lakona Sitakar; Fatimah Zuhrah (Yayasan Dar Arrisyah Indonesia, 2026)
The legal status of children born out of wedlock remains one of the most debated issues in contemporary Islamic family law, as it involves the intersection of lineage (nasab), child protection, and the development of national legal systems. The debate has intensified in Indonesia following the Constitutional Court Decision Number 46/PUU-VIII/2010, which recognized certain civil legal relationships between children born out of wedlock and their biological fathers. This development raises an important question regarding how the classical doctrine of lineage in Islamic jurisprudence can be reconciled with the growing demand for child rights protection within a modern legal framework. This study aims to analyze the status of children born out of wedlock from the perspectives of the major schools of Islamic jurisprudence, examine its regulation within Indonesian Islamic family law, and formulate a reconstructive model of the relationship between lineage and civil rights through the framework of maqāṣid al-sharī‘ah. This research employs a normative legal method using statutory, conceptual, and comparative approaches. Data were collected through library research involving classical Islamic legal sources, legislation, court decisions, and relevant academic literature. The findings indicate that the majority of Islamic legal schools reject the attribution of lineage between children born as a result of zina and their biological fathers, since lineage is legally established only through a valid marriage. In contrast, Indonesian Islamic family law has gradually recognized certain civil legal obligations arising from biological relationships. This study finds that the tension between classical Islamic jurisprudence and national law primarily stems from the absence of a clear conceptual distinction between lineage and civil legal relationships. Consequently, this article proposes a reconstructive model that separates lineage from civil responsibilities. Under this model, the protection of lineage (hifẓ al-nasl) is preserved, while the protection of children's rights is achieved through the recognition of biological fathers' civil obligations based on the principles of hifẓ al-nafs and hifẓ al-māl. This model offers a theoretical contribution to the development of a more adaptive and equitable Islamic family law in Indonesia.